Investigation of the corona discharge activity in liquid nitrogen under transient voltage conditions using fluorescent fiber sensor. (June 2022) - Naveen, Janjanam; Srinivasan, Balaji; Sarathi, R.
Highlights: In the present study, corona inception voltage in liquid nitrogen under standard lightning impulse voltage (SLIV) and oscillatory impulse voltages were studied using fluorescent fiber sensor. Under unidirectional oscillatory impulse voltage (UOIV) and sinusoidal bidirectional oscillatory impulse voltage (SBOIV) conditions, Corona discharge occurs around the peak of the first cycle. When the applied voltage is increased, the discharges occur in the subsequent cycles. Under switching impulse voltage (SIV), corona discharge is noticed at the rising edge in positive polarity, whereas in negative polarity, it is observed at the falling edge. The corona discharge inception voltage (CDIV) is determined to be highest under Unidirectional Oscillating Lightning Impulse (UOLI) and lowest under SI. The negative polarity exhibits more temporal spread than the positive polarity under oscillating impulse voltages. Abstract: In the present study, corona inception voltage in liquid nitrogen under standard lightning impulse voltage (SLIV) and oscillatory impulse voltages were studied using fluorescent fiber sensor. A single discharge signal is observed near the peak of the applied SLIV. The amplitude of the fluorescent signal is high with positive polarity than under negative polarity. At higher voltages, the magnitude of the fluorescence signal increases and it shifts towards the rising edge of the applied voltage. Under unidirectional oscillatory impulse voltage (UOIV) and sinusoidal bidirectional oscillatory impulse voltage (SBOIV) conditions, Corona discharge occurs around the peak of the first cycle. When the applied voltage is increased, the discharges occur in the subsequent cycles. Under switching impulse voltage (SIV), corona discharge is noticed at the rising edge in positive polarity, whereas in negative polarity, it is observed at the falling edge. The corona discharge inception voltage (CDIV) is determined to be highest under Unidirectional Oscillating Lightning Impulse (UOLI) and lowest under SI. The negative polarity exhibits more temporal spread than the positive polarity under oscillating impulse voltages.